Pre-Natal Diagnosis of beta – Thalassemia by Chorionic Villous Sampling - Shazia Syed, Faiza Shafi, Lubna Yasmeen, Humera Noreen; Rizwana Chaudhry (Journal of Rawalpindi Medical College, 2009)
Background: To promote the utility of Chorionic Villous Sampling (CVS) for pre-natal diagnosis of beta thalassemia in at risk population and to highlight its demographic area distribution and effect of consanguinity. Method: This Cross Sectional Study was conducted in the Department of Gyne/Obstet-I, Holy Family Hospital, Rawalpindi, Pakistan, from June 1997 to June 2009. All 137 couples having either a previously affected conceptus/child with thalassemia or having strong family history of thalassemia, were recruited for the test. Samples collected by standard procedure were sent to Armed Forces Institute of Pathology, Rawalpindi for thalassemia detection. Results: In 12 yrs 137 mothers underwent CVS. Mean gestational age at the time of procedure was 12.6 weeks. Consanguineous marriage was seen in 119 cases. Largest group was ‘Punjabis’. 126 couples had a previously affected child with homozygous beta thalassemia and 11 had heterozygous beta thalassemia in their children. 95 cases had a family history of the disease. After DNA analysis, 30 cases (22%) were diagnosed to have homozygous beta thalassemia while 77(56%) were having heterozygous beta thalassemia. Report was normal in remaining 30 cases (22%). Early spontaneous pregnancy loss was seen in only 02 cases. Conclusion: Thalassemia is one of the commonly inherited crippling disorders. Its familial transmission must be checked by effective public awareness programme, pre marital screening, genetic counseling and pre-natal diagnosis by CVS.